Truth and politics toward a post-secular community - Dallmayr, Fred R. (Fred Reinhard), 1928- (State University of New York Press, 2022)
"Endorses the pursuit of paradigm shifts in our understandings of faith, truth, and nature to remedy the "underside" of modernity and thus to inaugurate a post-modern (but not anti-modern) and post-secular (but not anti-secular) view of the world"--